Metodologia de priorização da expansão da rede de distribuição de gás natural com base na sintaxe espacial: uma aplicação no setor residencial em Fortaleza - Bandeira, María Inés Viviana de la Quintana Brüggemann (2005)
The search for sustainability and for the highest efficiency in the supply of energy has lead to the gradual substitution of electric energy for the use of natural gas in the residential sector. This workdescribes a study aiming to formulate a methodology that gives support to the expansion of the natural gas network based on the analysis of the urban morphology obtained by the Space Syntax, and increasing the efficiency in the construction of that network by directing the supply of services to the places with the largest residential demands. The methodology ofADEMGAS- Analysis of Potential Demand for Natural gas according to the Space Syntax, allows us to identify the roads with potential demand for natural gas within a defined urban space and to determine the roads having priority for the supply of energy through the correlation of soil use and socioeconomic data. The work aims to classify and to group in the study area (a part of the city of Fortaleza) the areas of potential residential demand by considering some planning scenarios, thereby allowing us to establish expansion ways that will get priority for the network, according to political and market criteria. The methodology has an important application in cities like Fortaleza, whose soil use has high density dispersion in the system of activities and the use of natural gas in the residential, commercial, industrial or automotive sectors is still incipient.